A Case of Spontaneous Regression and Recurrence of Primary Vitreoretinal Lymphoma. (17th November 2022) - Kim, Yeji; Shin, Saeam; Lee, Seung-Tae; Lee, Christopher Seungkyu
ABSTRACT: Purpose: To report a case of primary vitreoretinal lymphoma (PVRL) showing recurrence after spontaneous regression, diagnosed with the aid of next-generation sequencing (NGS). Methods: Retrospective case report. Results: A 61-year-old immunocompetent Korean woman presented with subretinal lesions suspected of PVRL, which resolved spontaneously in 2 months. After 8 months, the lesion recurred and diagnostic vitrectomy was performed. The cytologic examination of the vitreous was indeterminate as there was only minimal vitreous opacity present at the time of surgery. NGS identified significant mutations including single nucleotide variants in MYD88 L265P, which is a unique hallmark of VRL, in vitreous sample, and the diagnosis of PVRL was made. Conclusion: This case showed PVRL can spontaneously regress almost completely, then recur, so careful ophthalmic and systemic follow-ups are warranted. When cytological confirmation is challenging due to the minimal disease involvement in the vitreous, NGS is effective in confirming the mutation profiles of PVRL.